The Effectiveness of Environment-Based Thematic Learning with Thematic Learning of Teacher and Student Books on Learning Outcomes of 4th Grade Students in Gedong Songo Elementary School - Widiastui, Agnesia Maya Kurnia; Mawardi, Mawardi; Astuti, Suhandi (Universitas Nusantara PGRI Kediri, 2019)
There are doubts about integrative thematic learning based on integrative environment or thematic books of teachers and students that must be used considering that both have their respective advantages, this non-equivalent design quasi-experimental study aims to describe the effectiveness of environment-based integrative thematic learning compared to integrative thematic learning based on teacher books and student books on the learning outcomes of 4th grade students of Gedong Songo Elementary School. Significance values ​​in the normality and homogeneity tests in this study were normally distributed and homogeneous. The results of the t test or different test show of -9,364 using the assumption of t-test for equality of means with Sig (2-tailed) experimental group 1 and experimental group 2 of 0,000. Based on these results it can be interpreted that Ho is rejected and Ha is accepted so that the learning outcomes using environment-based integrative thematic learning are significantly superior compared to the integrative thematic learning of teacher books and 4th grade students of Gugong Songo Elementary School.